Parallel computing in virtual machine: Beowulf computer cluster using virtualbox / Ruzali Hussein - Hussein, Ruzali (2009)
Parallel computing is preferable when dealing with advance computing problem such as in the area of aerospace, benchmarking, automotive, defenses, geophysics. The technology was exclusive for the riches, due to it was too expansive. Beowulf cluster computing was a break through for researchers, academicians and open source community as parallel computing is available for everyone. Using commodity hardware and free open sources software infrastructure it is sufficient to built a parallel computing system. However, the implementation of Beowulf Computer Cluster is still facing with complex configuration and setup. With virtualization, the complexity and time consuming of hardware implementation and setup can be reduced. This paper presented comparison analysis between Beowulf Computer Cluster in virtual machine and a real Beowulf Computer Cluster. The result shows that virtual machine is able to adapt Beowulf cluster technology to provide a general purpose parallel computing environment on a single mini notebook.